Evaluation of the Policy to Accelerate Stunting Reduction in Purwakarta Regency - Kurnia Irawati, Raden Roro Astrid; Elisa Susanti; Darto, Darto (Journal of Law, Politic and Humanities, 2025)
Stunting in Indonesia shows fluctuations in prevalence, with a significant downward trend only seen after 2018. Although the stunting rate in 2023 was recorded at 7.1%, disparities between regions are still a major concern. Purwakarta Regency, which has a strategic role in human resource development, faces a major challenge in reducing stunting rates. With a high dependency ratio, Purwakarta has the potential to experience a demographic disaster if stunting is not addressed immediately. This study uses a descriptive qualitative approach to describe the policy of accelerating stunting reduction in Purwakarta in 2000-2023. Data were collected through observation, interviews, and documentation with informants from various related agencies, including the Health Office and Bappelitbangda. The results show that although policies such as Purwakarta Regent Regulation No. 203 of 2021 and intervention programs have been implemented, policy effectiveness is still limited. The main problems faced are low community participation, data misalignment, and limited infrastructure and supervision. Policy evaluation based on indicators of effectiveness, efficiency, adequacy, and responsiveness shows the need for improvements in inter-sectoral coordination and increased human resource capacity to achieve better targets. These findings provide important insights for policies to accelerate stunting reduction in Purwakarta district, with a focus on cross-sector collaboration and resource optimization